Carbon monoxide inhibits hemotoxic activity of Elapidae venoms: potential role of heme. Issue 1 (February 2018) - Nielsen, Vance; Frank, Nathaniel; Matika, Ryan
Abstract Envenomation by hemotoxic enzymes continues to be a major cause of morbidity and mortality throughout the world. With regard to treatment, the gold standard to abrogate coagulopathy caused by these venoms is still the administration of antivenom; however, despite antivenom therapy, coagulopathy still occurs and recurs. Of interest, this laboratory has demonstrated in vitro and in vivo that coagulopathy inducing venom derived from snakes of the family Viperidae exposed to carbon monoxide (CO) is inhibited, potentially by an attached heme. The present investigation sought to determine if venoms derived from snakes of the Elapidae family (taipans and cobras) could also be inhibited with CO or with the metheme inducing agent, O -phenylhydroxylamine (PHA). Assessing changes in coagulation kinetics of human plasma with thrombelastography, venoms from Elapidae snakes were exposed in isolation to CO (five species) or PHA (one specie) and placed in human plasma to assess changes in procoagulant or anticoagulant activity. The procoagulant activity of two taipan venoms and anticoagulant activity of three cobra venoms were significantly inhibited by CO. The venom of the inland taipan was also inhibited by PHA. In sum, these data demonstrate indirectly that the biometal heme is likely bound to these disparate venoms as an intermediary modulatory molecule. In conclusion, CO may not just be a potential therapeutic agent to treat envenomation but also may be a potential modulator of heme as a protective mechanism for venomous snakes against injury from their own proteolytic venoms.